Clásicos en Escena Ayer y Hoy - María Teresa Amado Rodríguez (Classica Digitalia: Mito e (Re)escrita, 2019)
This volume, "Classics on stage yesterday and today" offers a valuable set of works about classical theater. It studies old works and also their reception and their presence in contemporary scenes of a significant number of countries. We can learn about some aspects of the greek tragedy and latin comedy, from structural elements to the analysis of characters or cultural features, but also its constant presence in modern stages and its exuberant vitality as seed for new works that appear continously in modern literatures